Rule of the commoner : DMK and the formations of the political in Tamil Nadu, 1949-1967 - Krishnan, Rajan Kurai; Sriramachandran, Ravindran; Subagunarajan, V. M. S. (Independent researcher) (Cambridge : Cambridge University Press, 2022)
The Dravida Munnetra Kazhagam (DMK) has been singular in heralding and establishing a firm regional polity among the Indian states after the Indian Union was inaugurated as a republic. Academic scholarship has often treated the DMK as a Tamil nationalist or ethno-nationalist formation without conceptual clarity or critical insight. Rule of the Commoner demonstrates with persuasive evidence that the DMK appealed to a federalist and not nationalist imagination. The DMK's combining of the non-Brahmin Dravidian identity and allegiance to Tamil language led to a counter hegemonic formation of the plebes and left populism. Drawing on Ernesto Laclau, the book argues that the DMK achieved the construction of a people as Dravidian-Tamil, with Tamil being the empty signifier of the social whole, Brahmin vs. non-Brahmin divide functioning as the internal frontier leading to the formations of the political. It elaborates the conceptual scheme under the three rubrics of Ideation, Imagination and Mobilization.
Introduction: Two scenes of departure -- Ideation -- Construction of 'Dravidian-Tamil' people -- The uses of language -- Human immanence -- Left populism -- Imagination -- The play is the thing -- Critical hermeneutics -- Counter-narratives -- Power of fiction -- Mobilization -- The grassroots -- The waves -- The eruption -- The climb.
Title from publisher's bibliographic system (viewed on 15 Jun 2022).
Keywords: Dravida Munnetra Kazhagam; Populism -- India -- Tamil Nadu -- History -- 20th century; Political parties -- India -- Tamil Nadu -- History -- 20th century; Tamil Nadu (India) -- Politics and government -- 20th century